Oxidative Stress and Inflammation Are Associated with Coexistent Severe Multivessel Coronary Artery Stenosis and Right Carotid Artery Severe Stenosis in Elderly Patients. (22nd December 2021) - Li, Xia; Guo, Dianxuan; Hu, Youdong; Chen, Ying
Abstract : Oxidative stress and inflammatory response are the main pathogenic pathways in atherosclerosis stenosis. This study is aimed at evaluating the roles of oxidative stress and inflammatory response in coexistent right carotid artery severe stenosis and severe multivessel coronary artery stenosis in elderly patients. Circulating levels of total oxidant status (TOS), lipid hydroperoxide (LHP), 8-isoprostane (8-IP), malondialdehyde (MDA), monocyte chemotactic protein-4 (MCP-4), amyloid A (AA), high-sensitivity C-reactive protein (hs-CRP), and tumor necrosis factor- α (TNF- α ) were measured by standardised laboratory test methods. Markers of oxidative stress and inflammatory response: levels of TOS, LHP, 8-IP, MDA, MCP-4, AA, hs-CRP, and TNF- α, were increased (P < 0.001 ) in elderly patient. These results suggested that oxidative stress and inflammatory response may be involved in carotid artery severe stenosis and severe multivessel coronary artery stenosis and measuring oxidative stress and inflammation biomarkers may also be a promising step in the development of an effective method for monitoring the severity of right carotid artery stenosis and multivessel coronary artery stenosis in elderly patients.